A field and laboratory investigation of kerb side inlet pits using four media types. (1st October 2019) - Sapdhare, Harsha; Myers, Baden; Beecham, Simon; Brien, Chris; Pezzaniti, David; Johnson, Timothy
Abstract: Kerb side inlets with adjacent leaky wells are an emerging tool to harvest stormwater and to reduce runoff volumes and peak flow rates. This is achieved by collecting the first flush runoff into kerb side storages and infiltrating this water into the surrounding soil, thereby also reducing stormwater pollutant loadings. The hydraulic performance of the kerb side inlet, filter media and surrounding soil are key factors in the performance of these systems. However, no field or laboratory data are currently available for the hydraulic performance of a kerb side tree inlet pit. In this study, 12 tree inlet pits were constructed and filled with various media types including gravel, water treatment solids (a recycled waste product), sandy loam and clay to examine (1) leaky well infiltration rates (2) emptying times of the wells and (3) the well capacity (runoff storage volume) before and after runoff filtering through the wells. Using a laboratory model, the water harvesting performance of the kerb side inlet plate was also examined for various road longitudinal slopes. Using the field and laboratory data, simulation of the well performance was undertaken using the Model for Urban Stormwater Improvement Conceptualisation (MUSIC) to assess the capacity of these systems to reduce runoff volumes at the residential street scale. It was hypothesised that the type of filter media used in leaky well systems has a significant impact on the infiltration rate, regardless of the native soil type through which the stormwater eventually infiltrates. The results showed that the infiltration rates of systems filled with gravel were significantly higher than for the other media types, and this was followed by water treatment solids, sandy loam and clay. The results of the MUSIC modelling indicated that 2.8% of the mean annual runoff volume in the catchment could be harvested by the systems at the case study site. It was found that selection of high infiltration rate media and regular maintenance are the key factors for maintaining long-term performance of these systems. Highlights: This study presented the performance of kerb side inlets and leaky wells in a residential street. The inlet filter media types included gravel, sandy loam, native clay and water treatment solids. The road runoff harvesting capacity of the kerb inlet plate reduced to almost zero when the road longitudinal slope was 5%. Modelling showed that the 28 inlets, together reduced the annual runoff from the residential street by 8.1%.